VARIAÇÃO SAZONAL DE ELEMENTOS-TRAÇO ASSOCIADOS AOS SÓLIDOS EM SUSPENSÃO NO ALTO RIO MADEIRA, AMAZÔNIA OCIDENTAL - Galvão, R. C. F.; Gomes, J. P. O.; Almeida, R.; Bastos, W. R.; Lacerda, L. D.; Bernardi, J. V. E. (Geochimica Brasiliensis, 2012)